2020
DOI: 10.2337/dc20-0456
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Sodium–Glucose Cotransporter 2 Inhibition: Insights From Large-Scale Proteomics

Abstract: Objective To assess the effects of empagliflozin, a selective SGLT2 inhibitor, on broad biological systems through proteomics. Research Design and Methods 3,713 proteins were quantified using aptamer-based proteomics in 144 paired plasma samples obtained from 72 participants across the spectrum of glucose tolerance, before and after 4 weeks of empagliflozin 25 mg/day. Biology of the plasma proteins significantly changed by empagliflozin (at false discovery rate-corrected p<0.05) was discerned through Ingenuity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 54 publications
2
35
0
Order By: Relevance
“…These benefits have long moved beyond its role as antidiabetic drugs, which bring SGLT2is to the forefront. Recent studies have also found that SGLT2is can modulate iron metabolism and maintain body iron homeostasis as well as cardiac iron homeostasis (31,32). Here, the role of ferroptosis in protecting myocardial function by SGLT2is has attracted more and more attention.…”
Section: Discussionmentioning
confidence: 99%
“…These benefits have long moved beyond its role as antidiabetic drugs, which bring SGLT2is to the forefront. Recent studies have also found that SGLT2is can modulate iron metabolism and maintain body iron homeostasis as well as cardiac iron homeostasis (31,32). Here, the role of ferroptosis in protecting myocardial function by SGLT2is has attracted more and more attention.…”
Section: Discussionmentioning
confidence: 99%
“…Of the metabolic benefits, SGLT2 inhibitors demonstrated a reduction of blood glucose, body weight, and as well as an improved insulin resistance in HFrEF patients [ 22 24 ]. A recent proteomic study revealed an increase in plasma GDF-15 by empagliflozin in patients with diabetes or impaired glucose tolerance [ 25 ], however, it is unknown whether the SGL2Ti mediated improvement of HFrEF is accompanied by a change in plasma of GDF-15 levels.…”
Section: Introductionmentioning
confidence: 99%
“…These results contrast to a prior study of empagliflozin, which reported that empagliflozin increased GDF‐15 levels. 20 However, there are important differences between our trial and the empagliflozin study. First, our study was much larger, involving 3549 patients compared with only 72 in the prior study.…”
Section: Discussionmentioning
confidence: 88%